Evaluating the Impact of Government Policies on Child Marriage Prevention in Rembang Regency - Najichah, Najichah; Rofiq, M. Khoirur; Khari, Faseeyah (Al-Mujtahid: Journal of Islamic Family Law, 2025)
This study aims to evaluate the effectiveness of government policies in preventing child marriage in Rembang Regency, focusing on both preventive and repressive efforts. A qualitative research design was employed, utilizing observations and in-depth interviews with key stakeholders, including the Office of Religious Affairs (Kantor Urusan Agama, KUA), the Social Affairs Office (Dinas Sosial), and the Religious Court (Pengadilan Agama). The findings reveal that government initiatives can be classified into two primary categories: preventive policies, such as the Child-Friendly Village (Desa Ramah Anak), the Child Protection Advocacy Team (Tim Advokasi Perlindungan Anak, KPAD), and PUSPAGA SAMARA (Pusat Pembelajaran Keluarga dan Pengembangan Keluarga Sejahtera Samara), and repressive measures, including the Family Report Book (Buku Laporan Keluarga) and GASPOL (Gerakan Anti Perkawinan Anak). Despite these efforts, the overall effectiveness remains suboptimal due to challenges such as the lack of synchronization between local regulations and national law, insufficient inter-agency collaboration, limited human resources and budget allocations, a literal interpretation of religious teachings, and entrenched patriarchal cultural norms. The study recommends aligning local regulations with Law No. 16 of 2019, enhancing coordination between relevant agencies, increasing human resource capacity, improving budget allocation, and adopting a culturally contextualized educational approach to tackle child marriage.Keyword: Marriage dispensation, Rembang, Preventive and Represive Efforts